A posterior cranial fossa lesion mimicking myasthenia gravis - Syed Wajihullah Shah; Maryam Khalil; Mansoor Iqbal; Arham Arif Kundi; Muhammad Hassaan (European Journal of Case Reports in Internal Medicine)
A 41-year-old male with prior diagnosis of seronegative myasthenia gravis presented with complaints of bilateral ptosis, dysphagia, nasal voice and nasal regurgitation. Despite treatment with pyridostigmine, there was lack of significant improvement in the symptoms. Further investigations, including antibody assays and nerve conduction studies did not support the diagnosis. Magnetic resonance imaging revealed a lesion in the posterior cranial fossa, consistent with meningioma, which was compressing surrounding structures. This case highlights the importance of imaging techniques and considering alternative diagnosis in patients with unusual presentations to ensure appropriate management.